Categorising the Tree Protection Legislative Provisions Implemented by Local Planning Authorities Globally - Nik Mohamed Sukri, Nik Adlin; Ismail, Zulhabri; Wan Ariffin, Wan Tarmeze; Mohd Nordin, Rumaizah (International Journal of Sustainable Construction Engineering and Technology, 2023)
This study aims to categorise the tree protection legislative provisions (TPLPs) being implemented by local planning authorities (LPAs) worldwide to protect their urban trees. Through inductive thematic analysis of content in numerous LPA websites and the legislation documents downloaded from the websites, this study identified five categories of TPLPs: 1) Tree Felling Prohibition, 2) Significant Tree Register Establishment, 3) Tree Conservation Area Designation, 4) Tree Preservation Order (TPO), and 5) Tree Protection Planning Conditions. The first TPLPs category is for LPAs to prohibit tree felling or other tree damaging activities without their consent. The second category is to allow LPAs establishing registers of trees that are considered significant for protection. The third gives power to LPAs to designate their conservation areas and protect the trees inside the areas. Next, the TPO is the orders made by LPAs to protect specific trees, groups of trees or woodlands in the interests of amenity. The final TPLPs category is about conditions imposed by LPAs on a grant of planning permission that requires the developers to retain and protect any tree. The comprehensive information gathered has also enabled and protected urban trees to be broadly categorised into two: 1) Regulated Trees, and 2) Registered Trees. Moreover, several concepts of urban tree protection were developed and described to elucidate the categorisation. The concepts are: “Prohibitive vs Directive” commands pertaining to approaches taken by LPAs to protect trees; “Specific vs Blanket” methods to declare the protected trees; and “To be Protected vs To be Preserved” status to explain implications of being in each of the protected urban tree categories.